Rancang Bangun Alat Fermentor Sangat Sederhana (FSS) Pada Perbanyakan Agensia Hayati Media Cair Sebagai Pengendali Organisme Pengganggu Tanaman (OPT) - Kaidi; Sukmayoga, Totok Dwi; Yuliatiningsih; R, Frisilia Meidy; Putri, Agustin Jaka (Politeknik Negeri Jember, 2025)
The practicum of liquid media biological agent multiplication at the Jember State Polytechnic Plant Protection Laboratory still experiences obstacles, especially the FSS installation, which often results in contamination. The main cause is the limitations of the very simple fermenter (FSS) tool, so an effective tool design solution is needed. This research was conducted with the following objectives: (1) Designing the FSS tool for the multiplication of liquid media biological agents, (2) Developing Standard Operating Procedures (SOPs) for the FSS tool for the multiplication of liquid media biological agents and (3) Testing the FSS tool for the multiplication of liquid media biological agents. The research was conducted at the Jember State Polytechnic Plant Protection Laboratory in May - November 2024 with funding from the Jember State Polytechnic PNBP. This research uses a descriptive method, visual observation of the FSS tool installation for the multiplication of several types of liquid media biological agents, observation of the success rate of uncontaminated ECG liquid media, and then the data will be displayed in the form of a graphic diagram. The results of the study indicate that: 1. The design of the FSS installation tool can be used for the multiplication of liquid agents, 2. Standard Operating Procedures (SOP) can be used as a guideline for the multiplication of liquid media biological agents, 3. The test results of the FSS installation tool on the multiplication of several liquid media biological agents showed a success rate of Beauverria bassiana 75%, Trichoderma sp 91.67%, Metarhizium sp. 83.33% and Paenibacillus 83.33%. The constraints are that the propagation room is less sterile and the inoculation process is still separate from the installation tool. The benefits of the FSS tool design on the multiplication of this biological agent can be recommended as a tool for practical activities in the multiplication of liquid media biological agents in the Laboratory of Plant Protection, Research and Community Service.